HCISSP study guide - Virtue, Timothy M., 1975-; Rainey, Justin (Amsterdam : Syngress, 2015)
The HCISPP certification is a globally-recognized, vendor-neutral exam for healthcare information security and privacy professionals, created and administered by ISCp2s. The new HCISPP certification, focused on health care information security and privacy, is similar to the CISSP, but has only six domains and is narrowly targeted to the special demands of health care information security. Tim Virtue and Justin Rainey have created the HCISPP Study Guide to walk you through all the material covered in the exam's Common Body of Knowledge. The six domains are covered completely and as concisely as possible with an eye to acing the exam. Each of the six domains has its own chapter that includes material to aid the test-taker in passing the exam, as well as a chapter devoted entirely to test-taking skills, sample exam questions, and everything you need to schedule a test and get certified. Put yourself on the forefront of health care information privacy and security with the HCISPP Study Guide and this valuable certification.
Information flow mappingMonitoring PHI information flows; Jurisdictional implications; Data Use and Reciprocal Support Agreement (DURSA); Data subjects; Data ownership; Legislative and regulatory updates; Treaties; International Safe Harbor Principles; Industry-specific laws; Policies, procedures, standards, and guidelines; Policies; Procedures; Standards; Guidelines; A Practical Example; Common security and privacy compliance frameworks; ISO; National Institute of Standards and Technology (NIST); NIST Interagency Reports (IRs); Common Criteria; Common criteria-certified product categories.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed December 30, 2014).
Keywords: Information storage and retrieval systems -- Medical care -- Security measures -- Examinations, questions, etc; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Medicine; Health & Biological Sciences; Medical & Biomedical Informatics; Electronic books; Examinations; Electronic books